Single Cell Sequencing of the Pineal Gland: The Next Chapter - Coon, Steven L.; Fu, Cong; Hartley, Steven W.; Holtzclaw, Lynne; Mays, Joseph C.; Kelly, Michael C.; Kelley, Matthew W.; Mullikin, James C.; Rath, Martin F.; Savastano, Luis E.; Klein, David C. (Frontiers in Endocrinology, 2019)
The analysis of pineal cell biology has undergone remarkable development as techniques have become available which allow for sequencing of entire transcriptomes and, most recently, the sequencing of the transcriptome of individual cells. Identification of at least nine distinct cell types in the rat pineal gland has been made possible, allowing identification of the precise cells of origin and expression of transcripts for the first time. Here the history and current state of knowledge generated by these transcriptomic efforts is reviewed, with emphasis on the insights suggested by the findings.